Short selling meets hedge fund 13F: An anatomy of informed demand - JIAO, Yawen (Institutional Knowledge at Singapore Management University, 2016)
The existing literature treats the short side (i.e., short selling) and the long side of hedge fund trading (i.e., fund holdings) independently. The two sides, however, complement each other: opposite changes in the two are likely to be driven by information, whereas simultaneous increases (decreases) of the two may be motivated by hedging (unwinding) considerations. We use this intuition to identify informed demand and document that it exhibits highly significant predictive power over returns (approximately 10% per year). We also find that informed demand forecasts future firm fundamentals, suggesting that hedge funds play an important role in information discovery. (C) 2016 Elsevier B.V. All rights reserved.